2004
DOI: 10.1182/blood-2003-06-1937
|View full text |Cite
|
Sign up to set email alerts
|

Immune evasion proteins of human cytomegalovirus do not prevent a diverse CD8+ cytotoxic T-cell response in natural infection

Abstract: Although cytomegalovirus (CMV) expresses proteins that interfere with antigen presentation by class I major histocompatibility complex (MHC) molecules, CD8 ؉ cytotoxic T cells (CTLs) are indispensable for controlling infection and maintaining latency. Here, a cytokine flow cytometry assay that employs fibroblasts infected with a mutant strain of CMV (RV798), which is deleted of the 4 viral genes that are responsible for interfering with class I MHC presentation, was used to examine the frequency and specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 54 publications
11
96
1
Order By: Relevance
“…The same may be true for other structural proteins that are prominent targets of CD8 + T-cell memory responses (Boppana & Britt, 1996;Elkington et al, 2003;Sylwester et al, 2005). Another Achilles heel of HCMV is the requirement for high-level expression of IE proteins that are also highly immunogenic (Borysiewicz et al, 1988;Kern et al, 1999;Manley et al, 2004;Sylwester et al, 2005). Peptides from IE1, for example, are already presented to CD8 + T-cells at 6 h p.i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same may be true for other structural proteins that are prominent targets of CD8 + T-cell memory responses (Boppana & Britt, 1996;Elkington et al, 2003;Sylwester et al, 2005). Another Achilles heel of HCMV is the requirement for high-level expression of IE proteins that are also highly immunogenic (Borysiewicz et al, 1988;Kern et al, 1999;Manley et al, 2004;Sylwester et al, 2005). Peptides from IE1, for example, are already presented to CD8 + T-cells at 6 h p.i.…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical phase in the lytic cycle of the virus, as both exogenously introduced structural proteins and regulatory IE proteins are present in abundance at this time postinfection (p.i.). Both classes of proteins, in particular pp65 and IE1, serve as dominant sources of antigenic peptides presented by MHC I (Borysiewicz et al, 1988;Jackson et al, 2011;Kern et al, 1999;Manley et al, 2004;Wills et al, 1996). It has been shown that MHC class I molecules are retained in the ER under infection conditions that allow expression of only IE proteins of HCMV (Ahn et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the frequency and speciWcity of CD8+ CTL, a recent study using Wbroblasts as antigens presenting cells infected with a mutant strain deleted of the US immunoevasins, showed that most eVector T cells were directed against IE and E antigens [17]. These data suggest that after primary infection in vivo, naïve T cells could be activated by DCs which acquired IE and E proteins available before the time point at which US immunoevasins are expressed in amounts suYcient to exert their blocking activities.…”
Section: T Cell Repertoire Against Hcmv Exhibits a Broad Pattern Of Smentioning
confidence: 97%
“…the abundance of the major T-cell antigen pp65 (Varnum et al, 2004), renders these particles attractive for the development of a vaccine. However, recent studies showed that non-structural antigens, such as IE proteins, may also contribute significantly to the priming of a natural T-cell response against HCMV in humans ( Elkington et al, 2003;Khan et al, 2005;Manley et al, 2004;Sylwester et al, 2005). It was thus mandatory to show that DB can be modified to include additional antigens not normally present in these particles and that these antigens can be introduced successfully into the MHC class I presentation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provided evidence that peptides derived from exogenously delivered, particle-associated HCMV proteins are presented by MHC class I molecules without requiring de novo protein synthesis (Besold et al, 2007;Manley et al, 2004;McLaughlin-Taylor et al, 1994;Pepperl et al, 2000;Reddehase et al, 1984;Riddell et al, 1991). It was previously unknown whether peptides not usually included in viral particles would also be introduced into MHC class I presentation.…”
Section: Mhc Class I Presentation Of the Ie1 Tmy Peptide Derived Frommentioning
confidence: 99%